Comparison Of Hawalah And Wadi'ah Agreements In Muamalah Law - Annisa Nur Febriana; Nursyahfitri, Nursyahfitri; Muhammad Nur Iqbal (Sean Institute, 2024)
Study This aiming For analyze comparison between draft Wadi'ah and Hawalah . Research This use method study law bibliography , namely research conducted​ with method researching ingredients library or secondary data . Research This aiming For give understanding deep about phenomenon certain without do research field . Contract service in wadiah is contract custody goods or money between owner goods ( mudi ' ) with recipient deposit ( wadi' ). The purpose For guard security , safety and integrity goods or money that is deposited , while Contract wow is transaction finances involving​ transfer debt or not quite enough answer payment from One party to other parties . Analysis done For understand How second draft This functioning in context Islamic banking , as well as For identify differences and similarities between both of them . The results of the study show that Wadiah is transactions in which the bank acts as holder customer fund mandate , while Hawalah more focus on the transfer of funds between parties involved . Wadi'ah​ give security to customers , while Hawalah help in transfer of funds with fast and efficient.